Pengaruh Penerapan Sistem E-Filing, Pemahaman Peraturan Perpajakan, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Karyawan PT KAI (Persero) Divre III Palembang - Sopiyan AR; M.Thoyib; Indah Lestari (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
This research aims to analyze the effect of implementing the e-filing system, understanding tax regulations, and tax sanctions to employees taxpayer compliance of PT KAI (Persero) Divre III Palembang. This type of research is causal associative with a quantitative approach. The data used in this research is primary data in the form of a questionnaire distributed to employees taxpayer of PT KAI (Persero) Divre III Palembang with simple random sampling method. The population in this research were 2.652 employees taxpayer of PT KAI (Persero) Divre III Palembang. The sample used in this research was 97 respondents. The data analysis technique used is multiple linear regression analysis with the help of IBM SPSS version 26. The results of this research indicate that the implementation of the e-filing system has a positive and significant effect partially and simultant on taxpayer).). The R2 value obtained is 0,754, which means that the magnitude of the effect of implementing the e-filing system, understanding tax regulations, and tax sanctions on taxpayer compliance is 75,4% and the remaining 24,6% taxpayer compliance is influenced by other factors in outside the variables in this study. The independent variable that has the most dominant influence on taxpayer compliance is understanding of tax regulations with a regression coefficient (β) of 0,334.